Lipid nanoparticles for antisense oligonucleotide gene interference into brain border-associated macrophages - Calero, Macarena; Moleiro, Lara H.; Sayd, Aline; Dorca, Yeray; Miquel-Rio, Lluis; Paz, Verónica; Robledo-Montaña, Javier; Enciso, Eduardo; Acción, Fernando; Herráez-Aguilar, Diego; Hellweg, Thomas; Sánchez, Luis; et al. (Frontiers in Molecular Biosciences, 2022)
A colloidal synthesis’ proof-of-concept based on the Bligh–Dyer emulsion inversion method was designed for integrating into lipid nanoparticles (LNPs) cell-permeating DNA antisense oligonucleotides (ASOs), also known as GapmeRs (GRs), for mRNA interference. The GR@LNPs were formulated to target brain border-associated macrophages (BAMs) as a central nervous system (CNS) therapy platform for silencing neuroinflammation-related genes. We specifically aim at inhibiting the expression of the gene encoding for lipocalin-type prostaglandin D synthase (L-PGDS), an anti-inflammatory enzyme expressed in BAMs, whose level of expression is altered in neuropsychopathologies such as depression and schizophrenia. The GR@LNPs are expected to demonstrate a bio-orthogonal genetic activity reacting with L-PGDS gene transcripts inside the living system without interfering with other genetic or biochemical circuitries. To facilitate selective BAM phagocytosis and avoid subsidiary absorption by other cells, they were functionalized with a mannosylated lipid as a specific MAN ligand for the mannose receptor presented by the macrophage surface. The GR@LNPs showed a high GR-packing density in a compact multilamellar configuration as structurally characterized by light scattering, zeta potential, and transmission electronic microscopy. As a preliminary biological evaluation of the mannosylated GR@LNP nanovectors into specifically targeted BAMs, we detected in vivo gene interference after brain delivery by intracerebroventricular injection (ICV) in Wistar rats subjected to gene therapy protocol. The results pave the way towards novel gene therapy platforms for advanced treatment of neuroinflammation-related pathologies with ASO@LNP nanovectors.